Lung Cancer Surgery Part A: Pulmonary Artery Reconstruction - Balci, Akin Eraslan (Bentham Science Publ, 2013)
Reconstruction of the pulmonary artery in association with lung resection is technically feasible with some morbidity and mortality. To obtain complete resection is always main aim. Non-small cell carcinoma of the lung invading the PA has traditionally been treated by pneumonectomy. Sleeve resection and prosthetic reconstruction of the pulmonary artery (PA) has progressively gained acceptance as an alternative to pneumonectomy in lung cancer surgery. When the tumour involves the central PA, lobectomy associated with reconstruction of the PA with or without bronchoplasty is the only alternative to pneumonectomy. Pulmonary arterioplasty has come into more widespread use to achieve R0 resections while preserving lung parenchyma in patients with central primary cancers or metastatic N1 disease. This procedure preserves the lung parenchyma safely, resulting in a better postoperative quality of life.
Keywords: Lung cancer; pulmonary artery; sleeve; reconstruction